Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Fourteenth Annual ACM-SIAM Symposium on Discrete Algorithms 2020
DOI: 10.1137/1.9781611975994.135
|View full text |Cite
|
Sign up to set email alerts
|

Approximately counting and sampling small witnesses using a colourful decision oracle

Abstract: In this paper, we prove "black box" results for turning algorithms which decide whether or not a witness exists into algorithms to approximately count the number of witnesses, or to sample from the set of witnesses approximately uniformly, with essentially the same running time. We do so by extending the framework of Dell and Lapinskas (STOC 2018), which covers decision problems that can be expressed as edge detection in bipartite graphs given limited oracle access; our framework covers problems which can be e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Finally, we show that, whenever Φ is not meagre, the bipartite property Ψ Φ will satisfy the strong hardness condition in Theorem 5, yielding not only #W [1]-hardness, but also the conditional lower bound under ETH. 10 In what follows, we will describe both steps in more detail separately.…”
Section: Technical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we show that, whenever Φ is not meagre, the bipartite property Ψ Φ will satisfy the strong hardness condition in Theorem 5, yielding not only #W [1]-hardness, but also the conditional lower bound under ETH. 10 In what follows, we will describe both steps in more detail separately.…”
Section: Technical Overviewmentioning
confidence: 99%
“…For more general classes of properties, there are only partial results, and to the best of our knowledge the complexity of approximating #IndSub(Φ) is still open for edge-monotone properties. However, there are strong recent meta-theorems such as the k-Hypergraph framework due to Dell, Lapinskas, and Meeks [10] that yield efficient approximation algorithms for #IndSub(Φ) by reduction to vertex-coloured decision problems.…”
Section: Further Related Workmentioning
confidence: 99%
“…We do the improvement in approximation guarantee as well as query complexity in Rough Estimation algorithm (as stated in Theorem 1.3), as compared to Coarse algorithm of Dell et al [DLM20] (as stated in Lemma 5.1), by a careful analysis of the intersection pattern of the hypergraphs and setting the sampling probability parameters in Verify Estimate (Algorithm 1) algorithm in a nontrivial way, which is evident from the description of Algorithm 1 and its analysis.…”
Section: Somentioning
confidence: 99%
“…* In [BGK + 18], the oracle is named as Generalized Partite Independent Set oracle. Here, we follow the same suit as Dell et al[DLM20] with respect to the name of the oracle.…”
mentioning
confidence: 99%
“…Note that the Triangle-Estimation can also be thought of as Hyperedge Estimation problem in a 3-uniform hypergrah. Very recently, Dell et al [15] and Bhattacharya et al [8], independently, showed that the bound on ∆ E is not necessary to solve Triangle-Estimation by using polylogarithmic many TIS queries. Also, both Dell et al [15] and Bhattacharya et al [8], independently, generalized our result to c-uniform hypergraphs, where c ∈ N is a constant.…”
Section: Remarkmentioning
confidence: 99%